ADDRESSING SHARIA VALUES THROUGHOUT MARKETING STRATEGY OF SYARIAH HOTEL SOLO DISCOURSE ON INSTAGRAM - Arifin, Ferdi (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
This study aims to elaborate the marketing strategy of Syariah Hotel Solo addressing sharia values throughout the discourse on their Instagram account. The method employs qualitative because it is the most suitable to examine the data derived from social media Instagram. The result shows that the marketing strategy of Syariah Hotel Solo successfully reinforces their selling products and services, upholds religious teachings, and addresses sharia value as an accommodation business model. Moreover, the combination between visual and copywriting on each posts of Syariah Hotel instagrams strengthens their identity as a sharia business model that follows regulations from the Ministry of Tourism and Creative Economy and Indonesian Council Ulama at the same time.